(untitled) (Archives of Mechanics - Test, 2022)
For 2-dimensional problems in peridynamics, the transfer functions of boundary traction are constructed. The peridynamic motion equation introducing the boundary traction is improved and used to solve some typical 2-dimensional deformation and fracture problems, including the uniaxial tension and pure bending of plate, and fracture of a plate with the small circular hole or central crack. The acquired numerical solutions are close to the analytical solutions of elasticity and numerical solutions given by the finite element method. The results show that the improved technique of exerting traction on a boundary surface is valid for calculating the deformation and failure of solid. It provides a new method and path for the analysis of traction boundary value problems in peridynamics.